Meetings of Lithuanian Terminologists from the Translation Services of EU Institutions: An Overview - Platelis, Edgaras (Vertimo studijos, 2018)
[full article and abstract in Lithuanian; abstract in English]The paper presents a short overview (2006 till the present) of terminology meetings, or- ganized in Brussels/Luxembourg by Lithuanian terminologists working with the Translation Services of EU institutions (the Council of the EU, European Commission, European Parliament, Court of Justice, Central Bank, Committee of Regions, Economic Committee, and Court of Auditors). It is argued that this history represents continuous and gradual evolution and approximation/consolidation of working methods and practices. Some examples of success stories in resolving the terminological differences of different EU institutions are presented. The paper also briefly presents the terminological exchange link between the EU institutions’ Lithuanian translation services on the one hand and Lithu- anian public authorities on the other. The implications of the “triple loyalty” of the EU translator are discussed: the loyalty to the “house style” and multilingual requirements of the EU institution vs. Lith- uanian institutions’ position vs. Lithuanian language principles. Furthermore, the paper concentrates on the issues raised in the meetings related to the use of metaphoric terms in EU translations (e.g., carbon footprint, whistleblowing, spill-over effect). The argument is presented that avoiding metaphor sometimes leads to unclear and imprecise translation or loss of terminological identity. To illustrate the political aspect of conveying important emphasis in a given term, the example of demarcated beds is presented. Furthermore, it is argued that re-terminologization of historicisms/dated words might be useful. Finally the paper presents terminological networking and outreach activities undertaken by the Lithuanian Translation Unit at the General Secretariat of the Council of the EU, including the recently created Facebook page „Europinės terminologijos aktualijos“.
Keywords: none